The video game as expressive frame. Aesthetics, rules and worlds of reference - Planells de la Maza, Antonio José (Anàlisi, 2011)
The summit of the electronic leisure claims games increasingly complex from the technical and narrative point of view. The present article departs from a conception of the video game as a narrative experience to study and to propose a typology of the game centred on framing a concrete world of reference. Across framing, the aesthetics and the rules, different types of gameworlds are constructed that range from the playful mímesis up to the persuasive subversion of the world of reference.